Correction: Reduction of late stillbirth with the introduction of fetal movement information and guidelines - a clinical quality improvement - Tveit Julie; Saastad Eli; Stray-Pedersen Babill; Børdahl Per E; Flenady Vicki; Fretts Ruth; Frøen J Frederik (BMC, 2010)
Abstract We have performed a full cross-validation of this clinical Femina data collection against the routinely collected data of the Medical Birth Registry of Norway to validate the estimates of reduced mortality in the total population. The original estimate of fewer deaths during the intervention with OR 0.7 remains virtually unchanged for the original data collection. The validation procedures revealed inaccuracies in data from the Medical Birth Registry of Norway for a partial comparison with mortality outside the study area, and we here correct this comparison. We present new, corrected and cross-validated data. Despite comparability issues, the most robust and cross-validated estimates confirm similar estimates of reduced mortality during the quality improvement intervention.